PENGARUH KARAKTERISTIK DAN PERSEPSI INDIVIDU TENTANG PERINGATAN BAHAYA MEROKOK PADA BUNGKUS ROKOK TERHADAP PERUBAHAN SIKAP PEROKOK AKTIF DILINGKUNGAN XXVII KELURAHAN PEKAN LABUHAN KECAMATAN MEDAN LABUHAN - Eva Nirwana Natalia Hutabarat; Mira Indrayani (Jurnal Maternitas Kebidanan, 2021)
The prevalence of smoking in Indonesian people is very high, especially in males; they consist of children, adolescents, and adults. Government Regulation on Pictorial Health Warning (PHW) on cigarette packs is it ended to protect people and change their attitude toward smoking habit by quitting it. The purpose of this study was to analyze the influence of individual characteristics and perceptions about the warning of smoking hazard on cigarette packs on changing the attitude of active smokers. The research used analytic survey method with cross sectional design. It was conducted at Lingkungan XXVII, Kelurahan Pekan Labuhan, Medan Labuhan Subdistrict. The population was 324 people, and 248 of them were used as the samples. The data were analyzed by using univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression analysis. The result of the research showed that education, knowledge, and perception on warning for the danger of smoking in advertisements had the influence on the change in active smokers’ attitude (p<0.05) at Lingkungan XXVII, Kelurahan Pekan Labuhan, while age, occupation, and smoking habit did not (p>0.05). the variable which had the most dominant influence was the variable of education. Active smokers who had high education, good knowledge, and had good perception on the warning for the danger of smoking on cigarette packs in the advertisements had the oppurtunity of 57% to change their attitude which indicated it was very difficult to change smokers’ attitude toward smoking since it has become a habit. It is recommended that the government, through the Health Agency, evaluate advertisements about warning for the danger of smoking on cigarette packs since many smokers do not change their attitude although the warning is clearly visible and understandable.